Synaesthesia and sexuality: the influence of synaesthetic perceptions on sexual experience - Nielsen, Janina; Krüger, Tillmann H.; Hartmann, Uwe; Passie, Torsten; Fehr, Thorsten; Zedler, Markus (Frontiers in Psychology, 2013)
Introduction. Synaesthesia is a phenomenon in which a certain stimulus induces a concurrent sensory perception; it has an estimated prevalence of 4 %. Sexual arousal as an inducer for synaesthetic perceptions is rarely mentioned in the literature but can be found sometimes in case reports about subjective orgasmic experiences. Aims. To examine whether synaesthetic perceptions during sexual intercourse have an impact on the sexual experience and the extent of sexual trance compared to non-synaesthetes. Methods. In total, 19 synaesthetes with sexual forms of synaesthesia (17 female; 2 male) were included as well as corresponding control data of 36 non-synaesthetic subjects (n = 55). Two questionnaires were used to assess relevant aspects of sexual function and dysfunction (a German adaption of the Brief Index of Sexual Functioning, KFSP) as well as the occurrence and extent of sexual trance (german version of the Altered States of Consciousness Questionnaire, OAVAV). Additionally qualitative interviews were conducted in some subjects to further explore the nature of sexual experiences in synaesthetes. Main Outcome Measures. Sexual experience and extent of sexual trance during intercourse. Results. Synaesthetes depicted significantly better overall sexual function on the KFSP with increased scores for the subscale “sexual appetence” but coevally significant lower subscale scores for “sexual satisfaction”. Sexual dysfunction was not detected in this sample. Synaesthetes depicted significantly higher levels of the subscales “oceanic boundlessness” and “visionary restructuralization” than controls using the OAVAV. Qualitative interviews revealed varying synaesthetic perceptions during the different states of arousal. Furthermore, synaesthetes reported an unsatisfactory feeling of isolation caused by the idiosyncratic perceptions. Conclusions. Synaesthetes with sexual forms of synaesthesia seem to experience a deeper state of sexual trance without, however,